Islamic Boarding Schools And The Development Of Sharia Economy In Indonesia - Adim, Abd; Prakoso, Firza Agung; Khamidah, Yuni Astriana; Sofa, Devi Maya; Ramdhani, Reviandy Azhar (Universitas Al-Amien Prenduan Sumenep, 2025)
Despite these institutional advances, existing studies still focus heavily on formal, state-centered actors, leaving the role of community-based religious institutions largely understudied theoretically. This article addresses this gap by examining the role of Islamic boarding schools (pesantren) in Islamic economic development from the perspective of Islamic political economy and institutional governance. Through conceptual mapping, thematic analysis, and theoretical synthesis, the article reconceptualizes pesantren as non-state actors embedded in the moral, social, and political foundations of the Islamic economic system. The findings demonstrate that pesantren function not only as educational institutions but also as moral infrastructure capable of shaping economic preferences, legitimizing halal practices, and influencing community-based economic behavior. However, this study finds that the limited contribution of pesantren to formal Islamic economic development is not due to normative or theological deficiencies. Rather, it reflects structural constraints arising from weak institutional integration, fragmented governance, and a state-market bias in policy design. The dominance of market-oriented and technocratic approaches has marginalized Islamic boarding schools (pesantren) to a symbolic or instrumental role, resulting in a persistent gap between the ethical aspirations of Islamic economics and their institutional realization. This article contributes to the literature by developing a conceptual framework that positions Islamic boarding schools as intermediary institutions connecting values, markets, and public policy. It argues that the sustainability and inclusiveness of Islamic economic development in Indonesia depend on repositioning Islamic boarding schools within an inclusive governance architecture. Therefore, integrating Islamic boarding schools into halal governance, Islamic social finance, and economic policymaking is not only a policy option but also a structural and normative necessity to preserve the transformative ethos of Islamic economics.